Dampak Ekonomi, Sosial dan Lingkungan Terhadap Ekowisata Berbasis Masyarakat - Putri, Emmita Devi Hari; Yulianto, Atun; Wardani, Dyah Mustika; Saputro, Lilik Edi (Jurnal Ilmiah Pariwisata, 2022)
This study aims to determine the effect of economic, social, and environmental aspects on Community-Based Ecotourism. This type of research is descriptive quantitative research with multiple regression analysis methods. The sampling technique used random sampling. The study results show that the economic aspect has no significant effect on community-based ecotourism. Meanwhile, social and environmental aspects have a significant influence on community-based ecotourism. The economic aspect is not the main factor in the development of ecotourism, so the economic aspect does not impact the development of community-based ecotourism. Social aspects, including cultural heritage, local wisdom, and socio-cultural tolerance, are the main factors in maintaining ecotourism. Environmental aspects, including accessibility and amenity factors, are determinants of tourist satisfaction when visiting a tourist attraction because both are important factors needed by tourists. Keywords: Economic, Social, Environmental, Ecotourism